1999
DOI: 10.1037/1099-9809.5.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic characteristics of mental disorders in five U.S. communities.

Abstract: The study examined the ethnic ratio of 16 DSM-III mental disorders among White, Black, Hispanic, and Asian Americans. A total of 18,126 residents from 5 sites and 2,939 residents from the Epidemiological Catchment Area's Los Angeles site were studied separately. Logistic regression analysis was performed. Results showed that Blacks were significantly less likely than Whites to have major depressive episode, major depression, dysthymia, obsessive-compulsive disorder, drug and alcohol abuse or dependence, antiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
5
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 22 publications
5
94
5
1
Order By: Relevance
“…In the United States, approximately 27% of Native Americans, 15% of the black and white populations, 14% of Hispanics, and 6% of Asian Americans reported "alcoholism" in a first-degree relative (Harford, 1992). These data are consistent with epidemiologic findings that Native Americans have the highest rates of AUDs and Asian Americans have the lowest rates, compared with other racial and ethnic groups in the United States (Grant et al, 2004;Zhang and Snowden, 1999).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In the United States, approximately 27% of Native Americans, 15% of the black and white populations, 14% of Hispanics, and 6% of Asian Americans reported "alcoholism" in a first-degree relative (Harford, 1992). These data are consistent with epidemiologic findings that Native Americans have the highest rates of AUDs and Asian Americans have the lowest rates, compared with other racial and ethnic groups in the United States (Grant et al, 2004;Zhang and Snowden, 1999).…”
supporting
confidence: 80%
“…Despite their underrepresentation in national surveys, existing data indicate that Asian Americans, as a whole, have approximately half the rates of lifetime and past-year AUDs of other ethnic groups (Grant et al, 2004;Substance Abuse and Mental Health Services Administration, 2005;Zhang and Snowden, 1999).…”
mentioning
confidence: 99%
“…One possible reason for the gender neutrality in our sample could be due to the exclusion of patients with a current major depressive episode, one disorder regularly found to be more commonly diagnosed among women (Angst, 1995). We also found no differences across our three groups based on race, which differs from previous reports that indicated that community-based Blacks have lower rates of most disorders than Whites, with the exception of phobia and somatization (Zhang & Snowden, 1999). Conversely, data do demonstrate that racial minorities have less access to mental health services and are less likely to receive needed care (USDHHS, 2001), which may help explain the higher proportion of Blacks in this study with current psychiatric disorders.…”
Section: Discussioncontrasting
confidence: 57%
“…Although most investigations report more depressive symptoms among Blacks as compared to whites (Jackson, 1997;Myers, Lesser, Rodriguez et al, 2002), a few report no racial differences (Gallo, Cooper-Patrick, & Lesikar, 1998;Husaini, Castor, Linn et al, 1990). Despite the suggestion that socioeconomic status may explain these differences (Frerichs, Aneshensel, & Clark, 1981;Riolo et al, 2005), other studies find race differences even after controlling for SES (Zhang & Snowden, 1999). These conflicting findings may partially be explained by a reliance on earlier epidemiological studies using geographically restricted community or clinical samples (DeVellis, 1993;Krishnan, Delong, Kraemer, et al, 2002;Patten, 2000) which have limited generalizability.…”
Section: Race Ethnicity and Depressive Symptomsmentioning
confidence: 94%